Performance characterization and benchmarking : traditional to big data : 6th TPC Technology Conference, TPCTC 2014, Hangzhou, China, September 1-5, 2014. Revised selected papers /: traditional to big data : 6th TPC Technology Conference, TPCTC 2014, Hangzhou, China, September 1-5, 2014. Revised selected papers. (2015) - Unknown
No abstract available